Population Alert School: Actualization Through Islamic Religious Education Approach - Rahmi; Ahmad Lahmi; Iswantir; Asrial; Amir Rizaan Rahiman; Supratman (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study aims to identify and analyze the forms of Population Alert School (Sekolah Siaga Kependudukan/SSK) actualization through Islamic Religious Education at SMAN 1 Bonjol, Pasaman Regency, West Sumatra. This research employed a qualitative approach with a case study design. Primary data were collected through semi-structured interviews with an Islamic Religious Education teacher, an SSK committee member, and three twelfth-grade students, while secondary data were obtained from relevant scientific literature and school documents. Data were analyzed using the Miles, Huberman, and Saldaña model, consisting of data collection, data reduction, data display, and conclusion drawing and verification. Data validity was strengthened through source triangulation, brief member checking, and audit trail documentation. The findings show that SSK actualization through Islamic Religious Education appears through curricular alignment, contextual learning, school habituation, and early student value awareness. SSK values are integrated into Islamic Religious Education through topics such as morality, responsibility, healthy social interaction, quality family formation, future planning, and environmental awareness. The novelty of this study lies in its case-based explanation of how population-related values are translated into Islamic Religious Education learning, school religious culture, and students’ everyday moral awareness. This study recommends strengthening SSK socialization and mapping SSK values into Islamic Religious Education teaching documents.